Tribute to religion / Flavio Conti ; translated by Patrick Creagh. - Conti, Flavio, 1943- 4 0 16; 5 (New York : HBJ Press, 1979)
Presents monumental shrines of faith that exhibit great architectural skill, and includes Angkor Wat, Cathedral of San Marco, Cuzco Cathedral, Cologne Cathedral, Old-New Synagogue, Notre Dame, Melk Monastery, and Hagia Sophia
Cathedral of San Marco, Venice -- Notre Dame, Paris -- Old-New Synagogue, Prague, Czechoslovakia -- Melk Monastery, Austria -- Cologne Cathedral, West Germany -- Hagia Sophia, Istanbul -- Cuzco Cathedral, Peru -- Angkor Wat, Cambodia
Translation of Il fasto della religione
Keywords: 2 -- 0; 6; d; 20; 2